A Chinese company’s investment strategy in South Africa: the case of Hisense - Kim, Yejoo (DIE ERDE – Journal of the Geographical Society of Berlin, 2016)
Hisense, a Chinese home appliance manufacturer, entered South Africa’s TV market in 1996 and the company has since expanded its operations. Now Hisense is one of the major players in the TV market in South Africa. The company’s success can be measured through a mix of the four P’s of marketing: price, product, promotion and place (distribution). The successful combination of strategies helped Hisense penetrate South Africa’s TV market and acquire a growing market share. As a result, Hisense has contributed to export-led economic growth, technology transfer and job creation, among other development-related benefits to the host country. However, at the same time Hisense has faced challenges including problems with labour relations, e.g. poor working conditions and violations of minimum wage regulations. Most of these problems are recurring issues. This shows that overcoming these challenges is not an easy task for Chinese investors operating in South Africa or elsewhere in Africa, and questions remain regarding whether Chinese investment can contribute to fostering Africa’s industrialisation as well as China’s soft power.